1998
DOI: 10.1021/ja970869q
|View full text |Cite
|
Sign up to set email alerts
|

Cycloaddition Reaction of Zirconacyclopentadienes to Alkynes:  Highly Selective Formation of Benzene Derivatives from Three Different Alkynes

Abstract: Zirconacyclopentadienes reacted with acetylenecarboxylates in the presence of a stoichiometric amount (2 equiv) of copper chloride to give benzene derivatives in high yields along with the formation of a copper mirror on the wall of the reaction vessel. Reactions of unsymmetrical zirconacyclopentadienes prepared from two different alkynes with acetylenecarboxylates gave benzene derivatives from three different alkynes in high yields with high selectivities. Preparation of unsymmetrical zirconacyclopentadienes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
2

Year Published

2000
2000
2011
2011

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(80 citation statements)
references
References 50 publications
1
77
0
2
Order By: Relevance
“…(2) in Scheme 4]. [14][15][16][17] In this work, we found that three triple bonds out of four [shown in Eq. (3) in Scheme 4] could be highly selectively integrated into a benzene derivative; one of the triple bonds in bis(alkynyl)siScheme 2.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…(2) in Scheme 4]. [14][15][16][17] In this work, we found that three triple bonds out of four [shown in Eq. (3) in Scheme 4] could be highly selectively integrated into a benzene derivative; one of the triple bonds in bis(alkynyl)siScheme 2.…”
Section: Resultsmentioning
confidence: 89%
“…[2,14,16] In our work, treatment of zirconacyclopentadiene derivatives 4, generated in situ from bis(alkynyl)silane 1 and monoalkynes via zirconacyclobutene intermediates 2, with one equivalent of DMAD in the presence of CuCl afforded benzene derivatives 14 in high isolated yields (Scheme 5). The structure of 14 b has been determined by single-crystal X-ray structural analysis (Figure 1).…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Previously we reported that coupling of a zirconacycle with a third alkyne like dimethyl acetylenedicarboxylate (DMAD) in the presence of CuCl gives benzene derivative. 7 A similar procedure worked in 2a to afford phenylenethiophene co-oligomer 4a in 68% isolated yield. By employing different kinds of third alkyne we could produce a large variety of phenylene derivatives, furthermore, the functional groups on the phenylene unit could be utilized for further structural modification.…”
Section: Di-zcp 2bmentioning
confidence: 99%
“…Initial attempts to cyclotrimerise 6 with catalysts [50±52] such as [Pd(PhCN) 2 Cl 2 ], [53] Me 3 SiCl and Pd/C, [54] [Cp 2 ZrCl 2 ] [55,56] and [Co 2 (CO) 8 ], [57] failed without any reaction. Ligands with high steric hindrance (1,1'-bis(diphenylphosphino)ferrocene nickel(ii) chloride, dichloro-bis(tri-n-butylphosphine)nickel-(ii)) were also tried without the desired result.…”
Section: Introductionmentioning
confidence: 99%